Local Site of Saoraja Sawitto Traditional House as a Source of Historical Learning for Students - Al Islami, Achmad Idrus; Agustang, Andi; Syukur, Muhammad (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This study aims to determine the history of the Saoraja Kingdom of Sawitto, the use of the local site of the Saoraja Sawitto Traditional House as a source of historical learning, supporting and inhibiting factors of the local site of the Saoraja Sawitto Traditional House as a source of historical learning. The research method used is the historical method with 4 steps: Heuristics, Criticism, Interpretation, and Historiography. Based on the research conducted, it was found that the Saoraja Sawitto traditional house is the palace house of the Sawitto Kingdom which was previously made of wood. But, during the colonial era, there was a change in the building structure which then changed shape into a stone house. With the presence of the local historical site Saoraja Sawitto, students become active and enjoy learning, thus facilitating the teaching and learning process, especially in history subjects. One of them supporting factors for the use of this house are the enthusiasm of the students, and one of the inhibiting factors is the lack of literature regarding the Saoraja Sawitto traditional house.